(untitled) (Global Journal of Science Frontier Research, 2019)
A balanced nutrition for enhanced nutrient use efficiency is important to achieve potential crop yield. A deficiency of secondary and micronutrients is known to impair growth and quality of oil seed crops such as sunflower. The present study examined the effect of foliar application of nano-scale zinc particles in combination with boron on the growth and yield attributes of sunflower cv. RFSH-130 in a controlled environment. The treatments comprised foliar application of different nanoparticles (ZnS @ 400 ppm and ZnO @ 1000 ppm) and conventional ZnSO 4 @ 5000 ppm at 35 and 55 DAS. Further, these were combined with or without spray of boron @ 0.5% at 40 DAS. The sizes of the green synthesized nanoparticles of ZnS and ZnO in the presence of a biopolymer, chetosan were 60 and 38 nm respectively. ZnS and ZnO in nano formulations were absorbed by sunflower foliage to a greater extent compared to bulk ZnSO 4 . The results revealed that green synthesized ZnS and ZNO nanoparticles enhanced the growth and yield of sunflower.